Ellen G. White, co-founder of the Seventh-day Adventist Church - Graham, Roy E. (American university studies / 7, 1985)
Introduction, 1. Sources for the study of Ellen G. White, 2. The life and times of Ellen G. White, 3. The acceptance and use of Ellen G. White's work in the Seventh-day Adventist church, 4. Ellen G. White's influence in the formative period of the SDA church, 5. Ellen G. White and the bible, 6. Is Ellen G. White a prophet?, 7. Ellen G. White's influence on SDA approaches to race relations, 8. Ellen G. White's influence on SDA approaches to ecumenism, 9. Ellen G. White and her critics, 10. Theological reflections and some conclusions, Appendix, Bibliography